The impact of E-government on air quality: new evidence from China - Han, Huichao; Wu, Tianqi; Hai, Chenxi; Zhou, Nianchi (Frontiers in Environmental Science, 2023)
Air pollution has become an increasing concern in China. At the same time China has undergone a rapid shift from traditional government to E-government. Our study contributes to the existing literature by exploring the relationship between E-government and air pollution. This study investigates the impact of E-government on PM2.5 in 226 cities between 2012 and 2016. The results show that E-government has a significantly positive effect on air quality, the PM2.5 concentration will decrease by 6.71 percent with one percent increase in the E-government score. Furthermore, we find the impacts of E-government on air quality vary across cities. E-government has stronger effects of air quality improvements on more market-oriented cities and non-capital provincial cities, which illustrates although the government plays a leading role in the construction of E-government, its impact on the environment depends more on market dynamics. We also tested there exist three channels through which E-government affects air quality, namely, promoting innovation, improving total factor productivity, and optimizing industrial structure. This study provides important references for the green transformation in the context of E-government.